Art Appreciation Aznan Omar's Solo Exhibition: Printing Satire - Desa, Noor Enfendi; Muhamad, Noor A’yunni; Arshad, Mohd. Fawazie; Ramli, Izzal Khairi (KUPAS SENI: Jurnal Seni dan Pendidikan Seni, 2022)
Artworks carry their own meaning based on the idea that an artist wants to share or convey. In this writing, there will be a discussion about art appreciation of the artworks which have been presented in the solo exhibition of Aznan Omar: Mencetak Satira which took place from July 23rd, 2011, to August 6, 2011. This art exhibition was held at the House of Matahati (HOM). His artworks are presented using the technique of metal casting or lost-wax casting. In the appreciation of artwork, two sculptures are randomly selected to be discussed. This writing uses the iconographic approach to art that has been introduced by Erwin Panofsky for a clearer understanding of art appreciation. From an iconographic point of view, Erwin Panofsky has developed three levels of appreciation and understanding of works of art. The three levels of appreciation include: pre-iconography; the second is iconographic analysis; and the third is iconological interpretation. The outcomes from this discussion will explain the understanding of iconology as part of the identification of items and iconography, which is more of the description and classification of subjects in art. Aznan Omar's artworks presented in this solo exhibition, satirical in nature, can be appreciated with the understanding that has been defined.